Molecular Profile of Metallo-β-Lactamase Producing Bacterial Isolates from Clinical Samples; South-South Nigeria Perspective - Akereuke, U.E.; Onwuezobe, I.A.; Ekuma, A.E.; Edem, E.N.; Uko, N.S.; Okon, R.S.; Bawonda, E.O.; Ekpenyong, E.N.; Акереуке, У.Є.; Онвуезобе, І.А.; Екума, А.Е.; Едем, Е.Н.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
One of the major clinical problems regarding β-lactam antibiotics resistance is attributed to metallo-beta-lactamases (MβL), which are a group of enzymes that is a subset of beta- lactamases belonging to group B of the Ambler classification, which causes hydrolysis of carbapenems. The study was conducted to check the prevalence of MβL and its genes (IMP, VIM, and NDM) among Gram-negative isolates. Methods. 312 clinical samples (urine and wound) were cultured, and antimicrobial susceptibility testing was performed using the conventional disk diffusion method. MβL-phenotypic detection was uncovered by standard bacteriological techniques, MβL genes were amplified using pre-determined conditions set on an AB19700 Applied Biosystem thermal cycler. Results. 157 (56.1%) Gram-negative and 123 (43.9%) Gram-positive were isolated. Escherichia coli 32 (11.4%) and Pseudomonas aeruginosa 32 (11.4%) were the most predominant. Providencia stuartii 3 (1.1%), Klebsiella ornitholytica 2 (0.7%), and Stenotrophomonas maltophilia 1 (0.4%) were some of the less predominant isolates. Imipenem and Ertapenem were the most sensitive, while Gentamicin, Amoxicillin-Clavulanate, and Ceftriaxone were the most resistant. Twelve species (7.6%) were identified as MβL producers. The VIM gene (12: 100%) was the predominant gene, followed by the NDM gene (6: 50%) and the IMP gene (2: 16.7%). Conclusions. The detection of blaVIM, blaNDM, and blaIMP genes in South-south Uyo is really worrisome, and proper infectious control measures should be taken in order to prevent outbreaks of MβL-producing Gram-negative bacteria isolated in Uyo, South South Nigeria.